Shear Performance of Reinforced Concrete T Beams Strengthened by Carbon Fiber-Reinforced Polymer Bars - Hussain Hassan Alhilli; Mahdi H. Al-Farttoosi (Salehan Institute of Higher Education, 2023)
The primary purpose of this work is to investigate the shear response of T-reinforced concrete beams strengthened for shear using the embedded through section (ETS) technique when subjected to a monotonic one-point load till failure. The experimental approach included an examination of the twelve reinforced concrete T-beams, including two reference beams without any strengthening and ten strengthened beams. The twelve beams were divided into two main groups, with and without stirrups. The main variables in every group were the spacing and angle of inclination of the carbon fibre-reinforced polymer (CFRP) bars. The beams were strengthened in shear with CFRP bars inserted in the centre line of the section with different spacings and angles of inclination. The experimental analysis was performed to study the effect of spacing and angle of inclination of the CFRP bars on the ultimate load capacity, load-strain relationships, and load-deflection relationships. Results showed that the ultimate load of the beams in group one with inclined CFRP bars (45°) increased by 29.7, 22.4, and 15.5% for beams with CFRP bar spacings of 10, 15, and 20 cm, respectively, compared with the reference beam. In group one (with stirrups), the beam with inclined CFRP bars (45°) and a spacing of 10 cm has an ultimate load higher than that with vertical CFRP bars (90°) with a similar spacing by 2.6%. By contrast, the beam with inclined CFRP bars (45°) and a spacing of 10 cm in group two (without stirrups) has an ultimate load higher than that with vertical CFRP bars (90°) with a similar spacing by 2.5%. Doi: 10.28991/CEJ-2023-09-10-04 Full Text: PDF